Evolutionary genomics of chirally-variable freshwater snails from the Hawaiian Islands - Davison, Angus (2022)
Snails are exceptional because they are the only group of animals that commonly show variation in their left-right asymmetry, outwardly visible as a right- (dextral) or left-coiling (sinistral) shell. In previous research it has been shown that rare sinistrals in two groups of snails are likely caused by a pathological mutation in a duplicated formin gene. In comparison, in snails in which sinistrality is common there is no evidence that reversed chirality is associated with pathology, yet the genes that determine this variation are unknown. I therefore initiated a study on the genomics of chirally-variable freshwater snails Pseudisidora and Erinna sp. from the Hawaiian Islands, in the first instance aiming to assess their evolutionary origins, as well as gene-flow between the chiral types, but with a longer term view to identify the gene that determines variation in asymmetry. Ordinarily, assembly of molluscan genomes is difficult because they are large and highly repetitive, minimally requiring long read DNA sequencing. Here, I first assembled a draft genome for a Pseudisidora species using a new “reference-assisted” method in MaSuRCA, using minimal input DNA and short Illumina reads. Analyses of whole genome sequences for eleven individuals from three islands (up to 40x depth and 20 million SNPs) then showed that the species are derived from a single colonisation event, likely from North America. The snails then diverged into two isolated groups of snails on Kauai and Maui. The sinistral snails found on Oahu are likely derived from an ancestor of the Maui snails, with evidence for a dispersal event and subsequent gene flow between dextrals and sinistrals on Kauai. Chiral variation is not likely associated with a deletion in either copy of the duplicated formin gene, Ldia1 or Ldia2, or a major deletion in the rest of the genome. However, the formin remains a good candidate, because the Ldia2 version in sinistrals has a coding change that is predicted to remove a focal adhesion kinase binding site, thus possibly altering cytoskeleton remodelling. This work therefore reveals the underlying evolutionary history of the species, will contribute to studies on the taxonomic status and conservation, and sets the stage for future work to identify the gene that enables variation in the left-right asymmetry of this genus.